Pee-Wee's big adventure [videorecording (DVD)] - Burton, Tim, 1958-; Hartman, Phil; Reubens, Paul, 1952-; Daily, E. G.; Holton, Mark. 1958-; Salinger, Diane; Omen, Judd (Distributed by Warner Home Video, 2008)
Pee-wee hits the open road to look for his missing bicycle and encounters riotous adventures with bikers, bums, cowboys, cons, a phantom trucker, and a waitress with wanderlust.